2017
DOI: 10.1021/acs.chemmater.6b05493
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Anion/Cation Substitution (Sr2+ → Ba2+, Al3+ → Si4+, N3– → O2–) on Phase Transformation and Luminescence Properties of Ba3Si6O15:Eu2+ Phosphors

Abstract: A series of promising cyan, green, and yellow emission (Ba, Sr) 3 (Si, Al) 6 (O, N) 15 :Eu 2+ phosphors were synthesized by a Pechini-type sol−gel ammonolysis method. Variations in luminescence properties and crystal structure caused by the modification of phosphor composition were studied in detail. The prefired temperatures of the precursors play a key role in the process of forming the final products. Under UV light excitation, the as-prepared Ba 3 Si 6 O 15 :Eu 2+ phosphor presents a strong cyan emission l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 122 publications
(37 citation statements)
references
References 72 publications
(111 reference statements)
0
35
0
Order By: Relevance
“…The crystal-field splitting of the Eu 2+ 5d levels can also affect the emission peak shift, affecting the position of the lowest 5d levels. Also, the crystal-field-splitting energy is based on the following equation: ,, In the above equation, D q is the crystal-field-splitting energy, R represents the distance between the central ion Eu 2+ and its ligands, z represents the anion charge, e is the charge of the electron, and r is the radius of the d wave function. If the value of D q is smaller, the emission peak will locate at the higher-energy direction.…”
Section: Resultsmentioning
confidence: 99%
“…The crystal-field splitting of the Eu 2+ 5d levels can also affect the emission peak shift, affecting the position of the lowest 5d levels. Also, the crystal-field-splitting energy is based on the following equation: ,, In the above equation, D q is the crystal-field-splitting energy, R represents the distance between the central ion Eu 2+ and its ligands, z represents the anion charge, e is the charge of the electron, and r is the radius of the d wave function. If the value of D q is smaller, the emission peak will locate at the higher-energy direction.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, many studies have systematically revealed the relationship between luminescence properties and the local coordination structure of Ce 3+ /Eu 2+ /Bi 3+ ions. These strategies containing a “covalency effect”, “crystallographic sites engineering”, and “component substitutions” have been widely approved to generate long-wavelength light. Xia’s group has reported plenty of Ce 3+ /Eu 2+ -activated oxide luminescent materials and revealed an underlying mechanism based on “crystallographic sites engineering” and “component substitutions” approaches, such as RbLi­(Li 3 SiO 4 ) 2 :Eu 2+ , Ca 10 M­(PO 4 ) 7 :Eu 2+ , and K 3 YSi 2 O 7 :Eu phosphors. , Liu’s group successfully designed “component substitutions” strategies to obtain excellent nitride luminescent materials. Besides, Li’s group, Wang’ group, Zhang’s group, and Im’s group also reported many photoluminescence-tunable and highly efficient Ce 3+ /Eu 2+ /Bi 3+ -activated luminescent materials based on crystal structure design and component substitution strategies. These researchers exploited many superior luminescent materials in the visible light region, and the corresponding “structure-luminescence” relationship was revealed. However, the corresponding studies and crystal structure design strategies are still deficient in the exploitation of NIR luminescent materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, deficiency of red light composition provides a comparatively elevated color temperature (i.e., CCT greater than 4500 K), whereas a lower color rendering index (i.e., CRI less than 75), which greatly limits its application in daily life (such as indoor lighting). [7][8][9][10][11][12][13] Alternatively, a white LEDs, based on near-ultraviolet (near-UV) chips (covered by blue, green, and red color phosphors) is feasible to prepare because its optical performance only depends on the phosphors. 12,14 Therefore, red phosphors perform an essential task in white LEDs with excellent performance.…”
Section: Introductionmentioning
confidence: 99%